Examined The Relationship Between Travel Anxiety and Destination Choice: Implications for Tourism Marketing: A Qualitative Study - Juliana, Juliana; Sihombing, Sabrina Oktaria; Antonio, Ferdi (LPPM Universitas BSI, 2023)
This qualitative study examined the relationship between travel anxiety and destination choice, specifically focusing on its implications for tourism marketing. Through in-depth interviews with individuals who have experienced travel anxiety, the study explored their past experiences and decision-making processes when selecting destinations. Participants were selected through purposive sampling, ensuring diverse travel anxiety levels and demographic backgrounds. Data analysis followed a thematic approach, using past tense verbs to capture participants' retrospective perspectives on their travel anxiety experiences. The findings revealed that travel anxiety significantly influenced destination choices, with various factors contributing to decision-making processes. Past tense verbs were employed to describe participants' experiences, emotions, and coping mechanisms during their previous travel experiences. These verbs highlighted the nuanced nature of travel anxiety and provided valuable insights into the specific triggers and manifestations of anxiety in different travel contexts. The implications for tourism marketing were identified through the lens of the findings. Strategies were proposed to address and alleviate travel anxiety, targeting specific stages of the decision-making process. Tourism marketers can tailor their marketing efforts to better accommodate and support individuals with travel anxiety, ultimately enhancing their overall travel experiences by comprehending the complex relationship between destination selection and travel anxiety. This study adds to the growing body of research on travel anxiety by shedding light on people's individual experiences and providing tourism marketers with practical implications. The long-term effects of marketing interventions on reducing travel anxiety and increasing destination satisfaction should be the subject of additional research.